Катастрофы: социально-экономические аспекты - Одинец, В. (Социология: теория, методы, маркетинг, 2000)
Due to analyses of the greatest catastrophes, their reasons and consequences, we can
conclude about the real threat for the further modern earth civilization existence. As
far as catastrophes cause human losses, and prevention of them, as well as liquidation
and minimization of their consequences are essentially limited in time and material
resources, in our opinion, conceptual theory of catastrophes should be constructed on
social and economic base with the use of system synergetic analysis. In the article, there
have been specified the following notions: catastrophe, emergency situation and a
state of emergency; there has been presented a catastrophe classification.